Business record management as a key of compliance and efficiency / Rostella Sid - Sid, Rostella (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Business Record Management can be defined as a field of management responsibility for the efficient and systematic control of the creation, distribution, use, maintenance, and disposition of business records. It is a vital process to achieve the efficiency and economy as well as to preserve the business records. Compliance and efficiency both also play a crucial role within organization in order to make sure the organization run smoothly. Adherence to applicable laws, rules, and industry standards that control how organization handle and manage their records is referred to as compliance.